Punishment and incarceration a global perspective - Deflem, Mathieu (Sociology of crime, law, and deviance ;, 2014)
This volume in the series Sociology of crime, law, and deviance deals with aspects of punishment, including sentencing, incarceration, and prison conditions, in a variety of settings at local, national, and/or regional levels. The book brings together some 14 scholars to contribute their respective chapters, each of the authors drawn from various parts of the world, thus ensuring a global perspective. The chapters in this volume address specific aspects of punishment, prisons, and incarceration based on the authors unique specialty and setting. The focus is explicitly comparative, analyzing punishment in different national and regional settings, and thus seeks to offer a global orientation. Both thematically and regionally diverse within the province of social and behavioral studies devoted to the study of punishment and incarceration, the chapters in this volume are also diverse in terms of theoretical approach and methodological orientation.